“Annyeong, Saranghae!!!”: A Phenomenological Study on the Effects of Parasocial Relationships between Adult Filipino K-pop Fans and their Idols - Ascue, Andrei Gabrielle S. (Animo Repository, 2023)
As a global sensation, K-pop, or Korean Popular Music, has cultivated fans from across the world. Fans exhibit their fanship diversely, which often culminates in parasocial relationships—a highly pervasive phenomenon involving one-sided relationships between a fan (the media consumer) and their idol (the media persona). This phenomenological study investigates these connections to see how parasocial relationships manifest in the behavior of Filipino K-pop fans and if it facilitates unhealthy practices in their finances and academic/work life. The paper utilizes semi-structured interviews through Google Meet. Through convenience sampling, 12 participants were sourced, all adults aged 18 years and above whose fanship longevity ranges from two years or more. Data analysis showed that parasocial relationship manifestations in fans have both positive and negative effects. The former includes the majority’s perception of K-pop as their source of inspiration, motivation, and productivity in their academic/work life alongside recreational activities. Stress and burnout were reported to be relieved when consuming K-pop content. Conversely, some negative behaviors include sacrificing their sleep and academic focus when engaging as fans. Splurging on merchandise was also found to be a negative tendency, as well as the creation of toxic spaces on Stan Twitter, and obsessive, unhealthy behaviors such as stalking. As these behaviors were described only by the minority, the researchers conclude that there are more positive manifestations of parasocial relationships among the participants.